(untitled) (San Francisco, 1995)
Most solutions being recommended today for improving corporate performance prescribe reducing hierarchy by changing organizational structure, altering boundaries, and overcoming barriers within the organization. The authors go much further, calling for a "boundaryless organization," and they consider much more than the traditional and the obvious boundaries that exist within organizations. This book grew out of work done by the authors as consultants hired by General Electric's CEO Jack Welch, who first approached them with the concept of a "boundaryless organization." Applying what they learned in the effort to transform the way GE did business and from numerous other examples, they consider the vertical, horizontal, external, and geographic boundaries that exist for organizations. The authors provide tools to help measure the degree to which boundaries exist, demonstrate the consequences of boundaries, and identify steps to eliminate them. David Rouse
Keywords: Organizational change,Industrial organization,Interorganizational relations